The impact of a novel transendometrial approach for caesarean myomectomy on obstetric outcomes of subsequent pregnancy: a longitudinal panel study. (28th August 2017) - Huang, SY; Shaw, SW; Su, SY; Li, WF; Peng, HH; Cheng, PJ
Abstract : Objective: To evaluate the obstetric and surgical outcomes of a novel transendometrial approach for myomectomy during caesarean section in subsequent pregnancies. Design: Longitudinal panel study. Setting: Chang Gung Memorial Hospital, Taiwan, with approximately 5000 births per annum. Population: Pregnant women complicated with uterine myoma. Method: Sixty‐three pregnant women who received transendometrial myomectomy during the first caesarean delivery reported a subsequent live pregnancy and planned an elective repeat caesarean delivery. Main outcome measures: Obstetric outcomes consisted of gestational age at birth, newborn weight, Apgar score, birthweight adequacy, uterine rupture, placental abruption, placenta praevia, placenta accreta, spontaneous preterm birth and preterm premature rupture of membranes. Surgical outcomes consisted of surgical time, blood loss, blood transfusion, postoperative fever, length of hospital stay and mean adhesion score. Result: The mean gestational age at birth and newborn weight at the subsequent caesarean section were superior to those at the first caesarean delivery. Spontaneous preterm birth, small‐for‐gestational‐age infants and preterm premature rupture of membranes occurred more often in the first pregnancy than in the subsequent pregnancy. The mean surgical time was shorter for the subsequent caesarean delivery than for the first caesarean delivery combined with myomectomy. The other surgical composite outcomes of blood loss, blood transfusion, postoperative fever, length of hospital stay and mean adhesion score were similar across the two stages of caesarean deliveries. Conclusion: The novel transendometrial approach for caesarean myomectomy may improve the obstetric outcomes of subsequent pregnancy without causing any additional immediate and long‐term adverse surgical outcomes. Tweetable abstract: Transendometrial caesarean myomectomy may improve future obstetric outcomes. Tweetable abstract: Transendometrial caesarean myomectomy may improve future obstetric outcomes.